Mechanized and irrigated coffee cultivation promotes physical subsurface constraints in Oxisols - Katherine Martinez Escobar; Laís Maria Rodrigues Silva; Keise Duarte Bacelar de Morais; Júlio César Lima Neves; Teogenes Senna de Oliveira (Revista Brasileira de Ciência do Solo)
ABSTRACT Soils of the Cerrados (Brazilian Savanna) are deep, well-structured, and well-drained, with flat to gently undulating terrain that favors mechanization for coffee cultivation. However, these soils are susceptible to compaction. This study aimed to assess the effect of mechanization on the physical characteristics of an Oxisol under irrigated coffee cultivation in the Alto Paranaíba-Minas Gerais State. We selected eight areas with different cultivars and years of Arabica coffee plantation, sampling five positions: right soil under the tree crown (RSC), right tractor lines (RTL), interrows (IR), left tractor lines (LTL), and left soil under the tree crown (LSC) at layers of 0.00-0.10, 0.10-0.20, 0.20-0.30, and 0.30-0.40 m. We conducted principal component analysis (PCA) and analysis of variance, comparing means through Tukey’s test (p<0.05). The PCA selected three principal components (PC1, PC2, and PC3) composed of 12 physico-chemical properties from a total of 27 evaluated. Total porosity (TP), mean penetration resistance (PRmean), volumetric moisture (θ) at 100 kPa (θ 100 kPa) and 300 kPa (θ 300 kPa) tensions, particle density (PD), and granulometric fractions (clay, fine sand, and coarse sand) were among the most influential attributes. Total porosity and PRmean demonstrated the existence of compaction in the tractor wheel tracks, particularly in the 0.00-0.20 m layer. The 3.5-year-old plantation did not show significant variations in these properties. The θ 100 kPa and θ 300 kPa were higher in the compacted areas, indicating increased water retention but potentially limiting aeration. Clay content increased with depth, while sand fractions decreased, influencing the soil susceptibility to compaction. The vigor of coffee plants, as identified by satellite images (NDVI), could not be fully associated with the physical constraints of the subsurface, as even areas with low vigor did not consistently correlate with poor physical properties in laboratory analyses. These findings highlight the complex interplay between soil physical properties and coffee plant performance, emphasizing the need for comprehensive management strategies in mechanized coffee cultivation.